Effects of Trichocompost and Azotobacter chroococcum on Damping-Off Suppression, Tomato Growth, and Yield in Rhizoctonia solani-Infected Soil - Luciana Kuara; A. Marthin Kalay; Adelina Siregar; Abraham Talahaturuson; Reginawanti Hindersah (Jurnal Agroekoteknologi, 2026)
Soil-borne diseases caused by Rhizoctonia solani and declining soil fertility remain major constraints to tomato production in tropical agricultural systems. This study investigated the effects of Trichocompost and Azotobacter chroococcum on damping-off suppression, plant growth, yield, and rhizosphere microbial populations in R. solani-infested soil. A greenhouse experiment was conducted using a completely randomized factorial design consisting of four Trichocompost dosages (0, 20, 40, and 60 t ha⁻¹) and four A. chroococcum concentrations (0, 0.1, 0.5, and 1.0%), each with three replications. Both biological agents significantly reduced damping-off disease and enhanced plant height, fruit number, fruit weight, and beneficial microbial populations, whereas no significant interaction was detected between treatments. Trichocompost at 40 t ha⁻¹ combined with A. chroococcum at 0.5% provided the most effective and agronomically efficient treatment for improving tomato performance under pathogen pressure. These findings demonstrate that integrating Trichocompost and A. chroococcum offers an environmentally friendly and sustainable strategy for suppressing soil-borne diseases, improving rhizosphere microbial activity, and increasing tomato productivity in tropical agroecosystems.